2008
DOI: 10.1248/cpb.56.1292
|View full text |Cite
|
Sign up to set email alerts
|

1-(2,4-Dihydroxyphenyl)-3-(2,4-dimethoxy-3-methylphenyl)propane, a Novel Tyrosinase Inhibitor with Strong Depigmenting Effects

Abstract: Abnormal pigmentation is related to a variety of cosmetic and clinical conditions including melasma, lentigo, age spots, inflammatory hypermelanosis and trauma-induced hyperpigmentation.1) A number of studies have been devoted to producing safe and efficient depigmenting agents. However, many popular depigmenting compounds either lack potency or produce undesirable side effects.Skin color depends on the type and quantity of melanin, a natural pigment produced by melanocytes. The major ratelimiting step in mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…In this study, we found that DP which was reported by Nesterov et al as a tyrosinase inhibitor [20] reduced melanin content in NHEM (Fig. 1) and in a reconstructed human skin model (Fig.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In this study, we found that DP which was reported by Nesterov et al as a tyrosinase inhibitor [20] reduced melanin content in NHEM (Fig. 1) and in a reconstructed human skin model (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, Nesterov et al, characterized a novel tyrosinase inhibitor: 1-(2,4-dihydroxyphenyl)-3-(2,4-dimethoxy-3-methylpheny) propane (DP) [20]. They isolated DP from a methanol extract of medicinal plant Dianella ensifolia and was subsequently synthesized and assigned the INCI name Dimethoxytolyl Propylresorcinol.…”
mentioning
confidence: 99%
“…MelanoDerm™ (MatTek Corporation, Ashland, Mass., USA), a viable reconstructed 3-dimensional epidermis containing normal human melanocytes and keratinocytes [13], was used and processed for pigmentation assessments according to the manufacturer's instructions as previously described [11]. Briefly, epidermal equivalents with an air-liquid interface were treated once every other day over 2 weeks with 50 mg of oil-in-water cream containing the active compounds at the mentioned concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…MelanoDerm™ (MatTek Corporation, Ashland, Mass., USA), a viable reconstructed 3-dimensional epidermis containing normal human melanocytes and keratinocytes [16], was used and processed for pigmentation assessments according to the manufacturer's instructions as previously described [15]. Briefly, epidermal equivalents with air-liquid interface were treated once every other day during 2 weeks with 50 mg of oil-in-water cream containing RAL 0.05% (1.8 m M ); the cream was applied using a small spatula rinsed with ethanol just before use.…”
Section: Methodsmentioning
confidence: 99%